Reasons of Household Spending on Basic Education - Khanal, Basudeb (Rupantaran: A Multidisciplinary Journal, 2022)
The principal objective of this study is to find the reasons for household expenditure on basic education. Hence, this paper explores the motives of household spending on basic education. In the course of this study, a survey was carried out among the 380 households to collect the data, and descriptive statistics were used to analyse and interpret the data. As a result, it has been found that the households are motivated to spend on their children's basic education to formulate human capital on them. Moreover, they devote their scarce resources to their children's basic education to make them competent in the labour market through which their future life will be decent.